Latest developments on application of heterogenous basic catalysts for an efficient and eco friendly synthesis of biodiesel: A review - Sharma Y.C.; Singh B.; Korstad J. (My University, 2025)
Heterogeneous catalysts are now being tried extensively for biodiesel synthesis. These catalysts are poised to play an important role and are perspective catalysts in future for biodiesel production at industrial level. The review deals with a comprehensive list of these heterogeneous catalysts which has been reported recently. The mechanisms of these catalysts in the transesterification reaction have been discussed. The conditions for the reaction and optimized parameters along with preparation of the catalyst, and their leaching aspects are discussed. The heterogeneous basic catalyst discussed in the review includes oxides of magnesium and calcium; hydrotalcite/layered double hydroxide; alumina; and zeolites. Yield and conversion of biodiesel obtained from the triglycerides with various heterogeneous catalysts have been studied. © 2011 Elsevier Ltd All rights reserved.